The effect of COVID-19 vaccination on 30-day mortality after cardiac surgery - Insights from the Israel national registries - Orit Blumenfeld; Alina Rosenberg; Michal Reuven; Inbar Caspi; Erez Sharoni; Dror B. Leviner (Elsevier, 2024)
Summary: Background: We compared the effect of perioperative COVID-19, before and after vaccination, on 30-day mortality after cardiac surgery. Methods: Data was extracted from several national registries. The study period was March 1st, 2020-March 31st, 2022. Results: 2594 adult patients underwent cardiac surgery before the availability of a universal COVID-19 vaccine. 33 patients were diagnosed with COVID-19 prior to surgery (mean age 58.3±10.0, mean length of time 73.6±60.1 days) and 7 patients were diagnosed with COVID-19 0-14 days after surgery (age 66.4±7.6). These were compared to 4426 patients who underwent cardiac surgery after the availability of a universal vaccine: 469 patients were diagnosed with COVID-19 prior to surgery (age 62.1±10.1, length of time 175.8±158.2) and 32 patients diagnosed with COVID-19 0-14 days after surgery (age 60.8±14.5). In patients diagnosed with COVID-19 prior to surgery, there was no excess 30-day mortality either before or after vaccination (1 (3.0%) vs. 57 (2.2%), respectively, P<0.8, and 8 (1.7%) vs. 87 (2.2%), respectively, P<0.5). Patients diagnosed with COVID-19 after surgery, but before vaccination, had significantly higher 30-day mortality compared to COVID-19 negative patients (2 (28.6%) vs. 56 (2.2%) respectively, P<0.0001). This excess mortality disappeared after universal vaccination (1 (3.1%) vs. 94 (2.1%) respectively, P<0.7). Conclusions: COVID-19, when diagnosed in the early post-operative period, was a risk factor for mortality before available vaccinations, but not after vaccination was widely available. Pre-surgery screening and post-surgical isolation is essential until vaccines are available. This data may be useful for patient management in future respiratory pandemics.